Developing Teacher Diversity in Early Childhood and Elementary Education The REACH Program Approach - Schroth, Stephen T. (Palgrave Macmillan US, 2018)
This book explores the effects of the REACH program (Recruiting and Enlightening through Access to and Communication with High-need schools), a seven-year initiative devised to help find, attract, and prepare diverse teacher candidates interested in working with young children. The book analyzes how the program, set at a national liberal arts college in the US, used the three R's: recruitment, retention, and recognition, to successfully draw in diverse educators for young children who then go on to became leaders and role models in their schools and communities. Chapters examine ways to provide the academic, social, and enrichment supports necessary for diverse teacher candidates and identify current teacher education practices that are effective as well as opportunities for change.